EFFECTIVENESS OF SOCIAL MEDIA PLATFORMS IN DISSEMINATING QUR’ANIC TEACHINGS AMONG CONTEMPORARY MUSLIMS - Sule, Muhammad Maga; Shehu Mainiyo, Attahir (Fakultas Agama Islam Universitas Islam As Syafi'iyah, 2023)
Social media platforms can be an effective tool for disseminating Qur’anic teachings among contemporary Muslims, as they provide a wide-reaching and accessible means of communication. In fact, social media platforms such as Facebook, Twitter, Instagram and YouTube have millions of users worldwide, including a significant number of Muslims. This, perhaps makes it possible to disseminate Qur’anic teachings to a wide audience quickly and easily, regardless of geographical location and language barrier. It thus provides accessibility to individuals with diverse backgrounds and abilities, making Qur’anic teachings accessible and available to a wide range of people at their fingertips. Social media as a means of disseminating knowledge and information that are vital for societal growth create a sense of virtual community among Muslims and enable them to connect and learn from each other, particularly on Qur’anic teachings. It is in line with this submission that this discusses the effectiveness of social media platforms in disseminating Qur’anic teachings among contemporary Muslims. Accordingly, this study has identified some of the social media platforms like Facebook, YouTube, Twitter, WhatsApp, Telegram, Instagram as the channels that are utilised for the dissemination of Qur’anic teachings in the cyber-world. The paper adopted qualitative survey where Interviews were conducted with seasoned social users. The researchers purposively selected seven participants for the study because they are Muslims and possessed the knowledge about the phenomenon investigated. Some of the findings of the study revealed that social media are effective channels for the dissemination Qur’anic teaching to the contemporary world.